Feeding Practice during Infancy: A Hospital Based Study (Jalalabad Medical Journal, 2025)
Optimal infant feeding practices are crucial for the nutritional status, growth, development, and ultimately the survival of infants and young children. Proper feeding of infants can reduce childhood mortality and morbidity significantly. This study was done to know the feeding patterns of the infants in the Sylhet region who were admitted into a tertiary care hospital. This hospital-based, cross-sectional study was carried out at Jalalabad Ragib-Rabeya Medical College Hospital, Sylhet, from January 2018 to June 2018. The aim of the study was to find out the feeding practices during the first year of life among hospitalized infants. For the study, 128 mother-child pairs were purposively interviewed. A questionnaire was used for data collection with the verbal consent of the mother. All the children were 1 month to 12 months old. One hundred and ten infants were given colostrum, but 18 children (14%) were given prelacteal feeds. All the children aged 1 to 3 months were given breast milk, but bottle feeding or formula milk was also introduced in 59% of cases during this period. Although breast milk was continued at a high percentage (72% in 10-12 month olds) during the first year of life, the rate of bottle feeding increased with advancing age. Early weaning was found to be very common, and in the majority of cases (>50%), rice or suji was given. Dietary diversity was very poor, as less than fifty percent of the infants above six months were given eggs, flesh food, or vegetables and fruits. Approximately 50% of infants in the age group 10-12 months were given commercial cereal or canned food. Continuation of breast feeding and offering colostrum to the infants were satisfactory. The main problems revealed from the study were early complementary feeding, poor dietary diversity, and a significant prevalence of formula milk and commercial canned foods or cereals.Jalalabad Med J 2023; 20 (1): 23-30